Single-molecule-magnet behavior in mononuclear homoleptic tetrahedral uranium(III) complexes - Pereira, Laura C J; Camp, Clément; Coutinho, Joana T; Chatelain, Lucile; Maldivi, Pascale; Almeida, Manuel; Mazzanti, Marinella (Inorganic chemistry, 2014)
The magnetic properties of the two uranium coordination compounds, [K(18c6)][U(OSi(O(t)Bu)3)4] and [K(18c6)][U(N(SiMe3)2)4], both presenting the U(III) ion in similar pseudotetrahedral coordination environments but with different O- or N-donor ligands, have been measured. The static magnetic susceptibility measurements and density functional theory studies suggest the presence of different ligand fields in the two compounds. Alternating-current susceptibility studies conducted at frequencies ranging from 95 to 9995 Hz and at temperatures in the 1.7-10 K range revealed for both compounds slow magnetic relaxation already at zero static magnetic field with similar energy barriers U ∼24 K.